FAKTOR YANG MEMPENGARUHI PERILAKU GEN Z TERHADAP KEPUTUSAN MEMBELI DALAM PENGGUNAAN APLIKASI TIK TOK - Rahmi Rosita; Rahayu Tri Utami (POLITEKNIK LP3I JAKARTA, 2023)
A phenomenon that has emerged recently is the shift in consumer buying interest from e-commerce based platforms to purchasing via tok tok as a digital platform. This research aims to describe 1. The influence of advertising on interest in buying 2. To determine the influence of the Tik Tok application on interest in buying. 3. To find out the influence of advertising and the Tik Tok application on interest in buying This research uses a quantitative type of research. The sample in this study was 60 residents of the city of Bekasi using the specified purposive sampling technique. The research instrument uses data analysis techniques and quasi-questionnaire questionnaires with instrument testing using multiple linear regression analysis methods with analytical requirements tests, hypothesis testing. The research results show that: 1, Advertising Advertising has a positive and significant effect on interest in buying, with a t-table value of 1.295 and a significance level of 0.000 F Table 2.39 and a significance level of 0.000 < 0.05. The magnitude of the influence of advertising and the Tik Tok application on interest in buying is 61.2%. Keywords : Tik tok application, advertising influence, purchase interest.